AN ANALYSIS OF COGNITIVE LEVEL USED IN ENGLISH SEMESTER TEST ITEMS OF SMPN 2 BANGKINANG - Syahdan Syahdan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2014)
The purpose of this research was to analyze the cognitive level used in English semester test items ofSMPN 2 Bangkinang from the seventh grade up to ninth grade. The cognitive level used in each itemswas classified measure the percentage to find the comparison referred to bloom’s taxonomy in findingthe right answer. Kind of this research was survey research which only analyzed what was in the fieldarea. In this research, the researcher collected 150 English semester test items. Each class theresearcher 50 items. The test were in form of multiple choices. Then, all of the items were classifiedbased on its classification. By classifying the items, the researcher found that there were 32 itemscategorized into remembering (Remembering/C1) with the percentage of 21,3%, there were 61 itemscategorized into understanding (Applying/C3) with the percentage of 21,3% and there were 25 itemscategorized into analyzing (Analyzing/C4) with the percentage of 16,7%. From the results of thisresearch it could be concluded that the cognitive level used in English semester test items of SMPN 2Bangkinang at seventh grade up to ninth grade were classified in the level of ”Understanding (C2)”with the percentage of 40,7% and the level of the difficulty of the test was in the middle level.